(untitled) (The Pakistan Development Review, 2005)
A woman’s access to health care, in physical, social, and psychological contexts, depends on her health beliefs and her socio-economic and demographic background. As in most developing countries, the health system in Pakistan is a combination of modern and traditional medicine, and the nature of care sought again depends on the individual’s health beliefs and background characteristics. This paper thus not only focuses on whether women seek help or not when sick, but also on the differentials that exist in the health-seeking behaviour among women with different backgrounds. It finds that less than half the women reporting any symptom related to reproductive tract infections seek help, while for some symptoms the proportion seeking help goes down to a mere one-fifth. The decision to seek help depends on a woman’s educational and economic status, the extent to which she is worried about the symptom, duration of experiencing the symptom, and inter-spousal communication about the symptom. Lack of finances to access any health service and considering the symptom as something common not needing attention are the two main reasons for not seeking help. The choice of the healthprovider consulted for a symptom is linked to the perceived cause of the symptom, but allopathic doctors are preferred by the majority of women seeking health care.